PENGARUH PENGGUNAAN SMARTPHONE TERHADAP HASIL BELAJAR MATA PELAJARAN IPS PESERTA DIDIK SMP MUJAHIDIN PONTIANAK - Ariyanto Ariyanto; Agus Sastrawan Noor; Sri Buwono (Universitas Tanjungpura, 2021)
AbstractThis research aimed to determine how the use of smartphones affected the learning outcomes of students in social science subject at Mujahidin Middle School Pontianak. This research used quantitative approach with the form being correlation research. The population of this research consisted of all students of class VII Mujahidin Middle School Pontianak, namely 31 students and the sample taken in this research was the entire population sampled. The variables studied were Smartphone Usage (X) and Social Science Subject Learning Outcomes (Y). Based on the data analysis that the researcher conducted, it was concluded that: 1) The use of students' smartphones at Mujahidin Middle School Pontianak obtained the results with the most category, namely 22 (71.0%) students had the moderate category. 2) The learning outcomes of social science subject at Mujahidin Middle School Pontianak seen from the Standard of Minimum Completeness (KKM, namely 70) indicated that 7 (22.58%) students were categorized as complete and 24 (77.42%) students were categorized as incomplete. 3) Based on Simple Linear Regression Analysis, the effect of using smartphone on student learning outcomes was obtained by the equation 62.178 + 0.153X, which meant the constant value was 62.178. The regression coefficient value of the Smartphone Usage variable was positive, namely 0.153. The magnitude of the effect of smartphone use on learning outcomes based on the results of the determination test was 12.9% while the remaining 87.1% was affected by other factors which were not examined in this research.Keywords: Use of Smartphones, Learning Outcomes